2022
DOI: 10.1007/s00402-022-04730-9
|View full text |Cite
|
Sign up to set email alerts
|

Arthrofibrosis is a common but poorly defined complication in multiligament knee injuries: a systematic review

Abstract: Purpose The purpose of this study is to systematically review multiligament knee injury (MLKI) outcome studies to determine definitions of arthrofibrosis (AF) and provide information about incidence, management as well as potential risk factors. Methods A systematic literature search was performed (PubMed and Cochrane library) following the PRISMA guidelines of operatively treated MLKI (Schenck II–IV) studies reporting the incidence of AF. Twenty-five stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 88 publications
0
1
1
Order By: Relevance
“…Nevertheless, a considerable rate of stiffness and subsequent LOA in both groups has to be acknowledged. In comparison to a recently published systematic review [9], the rate of LOA was higher in our study as the indication for early LOA was made generous in this study. This decision was based on a recent study that revealed significantly improved range of motion and functional scores of early LOA (within 6 month) compared to late LOA (> 6 month) [7].…”
Section: Discussioncontrasting
confidence: 50%
“…Nevertheless, a considerable rate of stiffness and subsequent LOA in both groups has to be acknowledged. In comparison to a recently published systematic review [9], the rate of LOA was higher in our study as the indication for early LOA was made generous in this study. This decision was based on a recent study that revealed significantly improved range of motion and functional scores of early LOA (within 6 month) compared to late LOA (> 6 month) [7].…”
Section: Discussioncontrasting
confidence: 50%
“…Heterotopic ossification may restrict knee joint movement, reduce its function, and in severe cases, require additional surgery. Arthrofibrosis, as another common but easily overlooked complication, occurred in 12.1% of knee dislocation patients ( 11 ). Knee dislocation often requires surgical treatment ( 12 ), and the optimal management is still controversial ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%